A null mutation in the photoreceptor guanylate cyclase gene causes the retinal degeneration chicken phenotype - Semple-Rowland, Susan L. (The National Academy of Sciences, 1998)
The retinas of the retinal degeneration (rd) chicken are fully developed and possess normal morphology at hatching but fail to respond to light stimulation. Analyses of retinal cGMP, the internal messenger of phototransduction, show that the amount of cGMP in predegenerate, fully developed rd/rd photoreceptors is 5–10 times less than that seen in normal photoreceptor cells. We show that the low levels of cGMP in rd chicken retina are a consequence of a null mutation in the photoreceptor guanylate cyclase (GC1) gene. Thus, the rd chicken is a model for human Leber’s congenital amaurosis. Absence of GC1 in rd retina prevents phototransduction and affects survival of rods and cones but does not interfere with normal photoreceptor development.